Peran Guru Penggerak dalam Eksistensi Kurikulum Merdeka - Dinda Azzahra; Yusutria Yusutria (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
The teaching profession has an important role in educational management. From here we will explain the role of driving teachers in the independent curriculum and the impact of the presence of the new curriculum, namely the Independent Learning Curriculum, which demands the role of teachers as the main guard of change to change mindsets and increase their competence to suit the demands of the new curriculum. The aim of this research is to provide an overview of the role of driving teachers in managing enjoyable learning using existing technology so that students are encouraged to improve their academic achievement. The type of research in this research is descriptive qualitative, namely using interview data collection techniques with teachers at schools. The data analysis technique used is in the form of notes on the results of the interviewees. The results of this research reveal that the real role of teachers in the Merdeka curriculum in the Merdeka learning era, especially the role as driving teachers, namely teachers in the Merdeka learning curriculum must be able to act as a driver to have professional teaching skills with the requirement of being able to manage the class effectively, being able to build effective relationships with students. and must be a person who is creative, innovative, skilled and has high enthusiasm to accompany teaching and learning activities at school.